Parents’ Acceptance of Educational Technology: Lessons From Around the World - Osorio-Saez, Eliana Maria; Eryilmaz, Nurullah; Sandoval-Hernandez, Andres (Frontiers in Psychology, 2021)
One of the long-term lessons from the school closures due to the global pandemic COVID 19, is that technology and parental engagement are the best levers to access education so as to bridge the achievement gap between socially disadvantaged children and their peers. However, using technology is not simple as bringing equipment into the school and home and initiating its usage; these are just the first steps into a more complex and ambitious achievement of using technology as a catalyst for a shift towards new learning models in remote and hybrid settings. A theoretical framework based on the theory of acceptance and use of technology (TAMs) and social cognitive learning theory (SCLT) was used to analyse data from a survey completed by 4,600 parents from 19 countries during the national lockdowns in 2020. Regression models and thematic analysis of open-ended responses were employed to identify factors that contribute to parental acceptance and use of technology in support of their children’s learning. Our results show that parents are more engaged in children’s learning when well-structured technological tools are provided or suggested by schools, and when parents are socially influenced by the opinions of other parents, teachers, children, the general public, relatives, etc. Conversely, they are less engaged when they perceive the technological tools to be challenging and beyond their knowledge or skills. The study’s findings have practical implications for governments and school leaders, who need to be aware of the factors likely to determine the use of technology at home and take action to meet parents’ needs when using technology to support learning.